Common analysis methods for gaseous and solid contaminants emitted from different pollution sources: a review paper - Mahmood Ajaj, Qayssar; Mohd Shafri, Helmi Zulhaidi; Wayayok, Aimrun; Ramli, Mohammad Firuz (EM International, 2022)
Cement is widely used for building construction and infrastructural purposes. In the last thirteen years, this product's global annual production has increased by 78 percent, to 4,200 Mtpa. However, cement factories have been found to be harmful to air quality, plantations, and houses. Dust emission occurs through all the stages of cement production, such as storage, frying, packing, and even in the transportation stage. Cement factories cause environmental contamination worldwide, including in developed countries facing problems related to managing and controlling pollution, and also enforcing stringent legislation to prevent it. By reviewing different studies concerning cement plant emissions, we observed that various mathematical and statistical models have been applied to analyse and determine the effect of these emissions on the environment. Our study is focused on these analytical and statistical methods for analysing gaseous pollutant and particulate matter emissions from various pollution sources, especially cement plants. Identifying the elements of emissions and the development stages of other authors' analysis methods allowed us to conduct the most precise report possible. Our study also depicts the determinants of these strategies and their advantages, limitations, and implementation variables. The findings of these other studies were discussed, and it was discovered that the output differed depending on the technique used. The frameworks utilised ranged from using a single model to two or more models, in order to compare or combine them. GIS was used as an additional tool to improve the model's functionality in several studies. Some authors used programming languages such as Python and R to make their models more realistic.